Qualidade de vida das vítimas de trauma cranioencefálico em Sergipe - Vieira, Rita de Cássia Almeida (2011)
In Brazil and in the world, the trauma constitutes a serious public health problem, not only by magnitude but also hitting productive young people. The perception of quality of life may reflect the level of satisfaction, social integration, well-being of victims of head brain trauma and remains a challenge for public health policies. It is a research study, a descriptive cross-sectional and quantitative approach, whose aim was to evaluate the quality of life of victims of head brain injury by the World Health Organization Quality of Life (WHOQOL) Bref. Data were collected at a Center of Medical Specialties and a public reference hospital in trauma of Sergipe, by the months of December 2009 to March 2010. We interviewed 47 victims of head brain trauma treated during the period January 2008 to December 2009. The results showed that trauma victims had a mean age of 29 years, most were male (91.5%), single (51.1%), from capital (74.5%), schooling <8 years (57.4%), with activity (70.2%). The trauma mechanism was traffic accident (61.7%), with reports of alcohol consumption (59.6%), who suffered cerebral contusion (n = 25), there are 10.5 months and stayed in hospital for 13, 5 days (median). After trauma, most victims report headache (n = 33) did not alter the marital status (87.2%) and resumed the occupation after the previous event (68.1%). The victims reported satisfaction with the quality of life (65.9%) and health (66%). The psychological domain had the highest average score in (68.4) and highest correlation was found between the physical domains and social relationships (0.903). The victims who returned to productive activity, higher mean score in the domain of social relations (79.9).